2018
DOI: 10.3389/fimmu.2018.01946
|View full text |Cite
|
Sign up to set email alerts
|

Treating Influenza Infection, From Now and Into the Future

Abstract: Influenza viruses (IVs) are a continual threat to global health. The high mutation rate of the IV genome makes this virus incredibly successful, genetic drift allows for annual epidemics which result in thousands of deaths and millions of hospitalizations. Moreover, the emergence of new strains through genetic shift (e.g., swine-origin influenza A) can cause devastating global outbreaks of infection. Neuraminidase inhibitors (NAIs) are currently used to treat IV infection and act directly on viral proteins to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 186 publications
(187 reference statements)
0
62
0
1
Order By: Relevance
“…Their use in animal experiments has shown to reduce the mortality of H1N1 and H3N2-infected mice. More importantly, in the retrospective study of human drug use, the use of statins is associated with a reduction in influenza-induced lethality (Liu et al 2009;Mehrbod et al 2014;Davidson 2018). Serotonin reuptake inhibitors can alleviate lung inflammation in mice induced by the H1N1 influenza virus and reduce mortality in mice (Sharma et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their use in animal experiments has shown to reduce the mortality of H1N1 and H3N2-infected mice. More importantly, in the retrospective study of human drug use, the use of statins is associated with a reduction in influenza-induced lethality (Liu et al 2009;Mehrbod et al 2014;Davidson 2018). Serotonin reuptake inhibitors can alleviate lung inflammation in mice induced by the H1N1 influenza virus and reduce mortality in mice (Sharma et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cytokine storms are directly associated with influenza-induced fatal acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) (Tisoncik et al 2012;Short et al 2014). Antiviral treatments, which target viral components, are prone to develop drug-resistant viruses and have a narrow time window for their administration; they are also unable to control the excessive proinflammatory response that occurs in the late stage of infection (Davidson 2018). Therefore, the attenuation of the host inflammatory response with immunomodulators may represent a good strategy for combating severe influenza.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only two antiviral drug classes, with some usefulness, are available and very few are under development or in trials [8]. The drugs available in the clinic are Matrix 2 (M2) ion channel inhibitors, (e.g., amantadine and rimantadine) and neuraminidase (NA) inhibitors (e.g., oseltamivir and zanamivir) [6].…”
Section: The Disease Of Influenza and Available Therapiesmentioning
confidence: 99%
“…37 Influenza benefits from both genetic drift and shift. 20,38 These dynamic instabilities produce vast amounts of variant viruses, many of which may be non-productive progeny. However, with each replicative cycle of the virus some amino acid compositional variationsmutations, are produced that do not compromise viral infection.…”
Section: Evasionmentioning
confidence: 99%